Evaluating Antibiotic Resistance in Pediatric UTIs: Five-Year Data from a Tertiary Hospital in Turkey - Fedli Emre Kılıç; Osman Küçükkelepçe (Medicina)
Background and Objectives: Urinary tract infections (UTIs) are common in children and account for 5–6% of febrile illnesses. This study aims to evaluate the bacterial pathogens isolated from pediatric UTI cases and their antibiotic resistance patterns to inform updated treatment guidelines. Materials and Methods: This retrospective study included 2753 children with positive urine cultures treated at Adıyaman Training and Research Hospital from January 2020 to June 2024. Data on patient demographics, bacterial culture results, and antibiotic resistance patterns were analyzed. Results: Among the 2753 patients, 71.1% were female and 28.9% were male, with a mean age of 54.6 ± 48.6 months. Escherichia coli was the predominant pathogen, isolated in 61.2% of cases, followed by Klebsiella pneumoniae (13.3%), Proteus mirabilis (9.1%), and Enterococcus faecalis (3.5%). Gender-specific differences showed that E. coli was more frequently isolated in females (71.7%), while Proteus was more common in males (18.5%). Antibiotic resistance analysis revealed high resistance rates to ampicillin (67.4% in E. coli and 100% in Klebsiella), TMP-SMX (33.2% in E. coli and 30% in Klebsiella), and cefixime (45.3% in E. coli). Amikacin showed the lowest resistance across all pathogens, with only 0.9% resistance in E. coli. The resistance to third-generation cephalosporins, particularly ceftriaxone and cefixime, has significantly increased over time, especially in the Klebsiella species. Conclusions: The results indicate high resistance to ampicillin and TMP-SMX. However, E. coli and other pathogens remain susceptible to nitrofurantoin, amikacin, and carbapenems, making these antibiotics viable for empirical therapy. Regional resistance should be considered when selecting treatments for pediatric UTIs to improve outcomes and reduce resistance development.